ЯНГИЛАНАЁТГАН ЎЗБЕКИСТОН: ЁШЛАР ТАРБИЯСИ СОҲАСИДАГИ ИСЛОҲОТЛАРНИНГ СТРАТЕГИК МОҲИЯТИ - Қадиров, Қ. (SCIENCE and SOCIETY, 2020)
The article discusses the strategic nature of reforms in the field of youth education. Increasing the scale and quality of spiritual and educational events organized in higher education institutions and ensuring their viability in the ideological education of the younger generation is also considered as the basis of today’s reforms.